Language Culture and Land Use: A Case Study of the Dialect Cultural Regions in Anhui Province, China - Xiyu Chen; Guodong Fang; Jia Kang; Bo Hong; Ziyou Wang; Wuyun Xia (Land)
The unity of material and spiritual civilization is among the important criteria for sustainable development and modernization construction. However, defining the relationship between the two has posed a challenge to researchers. In terms of spiritual civilization, many studies on dialect maps reflect the dialect characteristics and cultural features of different regions. Regarding material civilization, changes in land use and behavior have attracted the attention of many scholars, who have extensively discussed their regional heterogeneity. However, few studies have focused on the connection between the two, and discussions on the possible bidirectional interaction between dialects and land use have been limited. Thus, in order to bridge the gap between the spiritual civilization related to language and the material civilization related to land use, this study proposes an interactive theoretical framework and conducts an in—depth analysis by taking Anhui Province in China as an example. Firstly, it comprehensively identifies the dialect types within Anhui Province and maps the dialects. This fundamental work provides a crucial basis for understanding the distribution of different dialect regions. Subsequently, a profound analysis of the spatiotemporal changes in land use in this province over time is carried out. To further explore the characteristics of land use behaviors, this study employs the Latent Dirichlet Allocation (LDA) model to mine the latent semantic topics in the land use-related data, thus enabling a more detailed understanding of the diverse patterns of land use behaviors in different regions. Finally, by uncovering the characteristics of land use changes and behavior differences in different dialect regions, this study explores the possible bidirectional interaction mechanisms. The results show that significant spatial heterogeneity in land use behavior and its driving factors can be observed within different dialect regions. Its bidirectional interaction is manifested in land use behaviors regulating people’s activities through constructing “fields” and forming habits that influence regional dialects and cultures. Meanwhile, under mobility mechanisms, new dialect systems replace indigenous languages in immigration destinations. Land use methods from emigration areas are spread through convenient communication, affecting the cultural psychology and land use behaviors of social groups in immigration destinations. This study expands the boundaries of linguistic and cultural geography, offering a new perspective for the identification of spatial differentiation and new ideas for the governance of spatial differences.